#TITLE_ALTERNATIVE# - KHOIRUNNAS PRIYADI (NIM: 10313025), EKO
An open cluster is a group of stars that is bound in a single gravitational field, has 4-5 pc radius, and consists of dozens up to thousands of stars. One can find open clusters mainly at the Galactic disk. Open cluster detection can be done by separating cluster's member stars from foreground and background stars. Complete cluster detection is needed in order to quickly recognize high stellar number density, especially from all-sky survey star catalogues data. In this Bachelor's Thesis, open cluster is detected using non-parametric method, namely Hot Pixel and ScatterM. Both of these methods take stellar number density and star's proper motion into account. Among 131 open clusters at 250Ã‚Â° ≤ l ≤ 270Ã‚Â° and -10Ã‚Â° ≤ b ≤ 10Ã‚Â°, 87 clusters (66%) are successfully detected using Hot Pixel method, while ScatterM method only detect 66 clusters (50%). On the other hand, 28 clusters fail to be detected using the two methods, probably caused by field stars and molecular cloud disturbance at low galactic latitude (Ã‚Â± 2Ã‚Â°). Central proper motion shifting and incorrect choice of pixel width probably cause ScatterM method to detect less amount of clusters than the Hot Pixel method. Central proper motion difference between the two methods and MWSC II catalogue probably caused by proper motion data error, wide central proper motion calculation step, and the choice of radius in proper motion space. There are some pixels with high intensity that are suspected to be newly detected star clusters.